2001
DOI: 10.1081/ja-100103560
|View full text |Cite
|
Sign up to set email alerts
|

Peer Influences and Susceptibility to Smoking Among California Adolescents

Abstract: Using data from a diverse statewide sample of 10th-grade adolescents in California, in 1996-97, this study investigated the associations between peer influence variables and susceptibility to smoking. Peer influence variables included attitudes about the social consequences of smoking and subjective norms, as described by the Theory of Reasoned Action. Among never-smokers (N=2681) and ever-smokers (N=4248), attitudes about social consequences of smoking and subjective norms each were associated with an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 25 publications
2
46
1
Order By: Relevance
“…Since girls are more sociable than boys, they may be at particular risk of developing increasingly favorable attitudes to alcohol, suggesting that highly sociable girls could be the focus of such interventions. Prevention programs should also target correcting children's peer-based descriptive norms, which are typically overestimations of actual use (Unger, Rohrbach, Howard-Pitney, Ritt-Olson, & Mourrapa, 2001). We showed that children's hostility influenced intentions to drink alcohol through subjective norms.…”
Section: Discussionmentioning
confidence: 99%
“…Since girls are more sociable than boys, they may be at particular risk of developing increasingly favorable attitudes to alcohol, suggesting that highly sociable girls could be the focus of such interventions. Prevention programs should also target correcting children's peer-based descriptive norms, which are typically overestimations of actual use (Unger, Rohrbach, Howard-Pitney, Ritt-Olson, & Mourrapa, 2001). We showed that children's hostility influenced intentions to drink alcohol through subjective norms.…”
Section: Discussionmentioning
confidence: 99%
“…Odds ratios were calculated separately for 7th and 11th grade boys and girls. We used a stratified analysis because (1) adolescent substance use increases with age, both in the U. S. and in China (Independent Evaluation Consortium, Wave 1 Data, 1998; Unger, Rohrbach et al, 2001), and (2) smoking and alcohol use are gender-related social behaviors in China, in that prevalence rates for males are much higher than for females (Gong, Koplan, Feng, & Chen, 1995;Li, Fang, Stanton, Feigelman, & Dong, 1996;G. R. Liu, 1997;Liu et al, 2001).…”
Section: Data Analysesmentioning
confidence: 99%
“…Richardson et al (1989) found that students left alone after school were more likely to engage in cigarette smoking and other substance use behaviors. One reason is that unsupervised adolescents during after-school hours are more likely to spend time with peers, whose influence has been shown to lead to increased substance use (Richardson et al, 1989;Unger, Rohrbach, Howard-Pitney, Ritt-Olson, & Mouttapa, 2001;Unger et al, 2002). Peers are believed to contribute to adolescent substance use, including smoking and alcohol, both directly and indirectly through several mechanisms: by modeling drug use, by shaping norms, attitudes, and values; by exposing the adolescent to opportunities for drug use, by providing positive social reinforcement for attempted substance use.…”
mentioning
confidence: 98%
“…It is certainly true that if a person's friend smokes, they are also more likely to smoke themselves (Mayhew, 2000), particularly if there is peer approval of smoking (Morgan & Grube, 1989;Unger, 2001). One function of cigarette smoking is to facilitate entry into a peer group (Gilliard & Bruchton-Schweitzer 2001;Wiltshire, Amos, Haw & McNeill, 2005).…”
Section: The Role Of Peers and Friendsmentioning
confidence: 99%
“…Unger et al 2001), positioning the smoker as someone who does not particularly have to account for their actions.…”
Section: Normalisationmentioning
confidence: 99%